2017
DOI: 10.1177/0284185117735349
|View full text |Cite
|
Sign up to set email alerts
|

Combined transarterial chemoembolization and radiofrequency ablation for small treatment-naïve hepatocellular carcinoma infeasible for ultrasound-guided radiofrequency ablation: long-term outcomes

Abstract: Background Ultrasound (US)-guided radiofrequency ablation (RFA) for small hepatocellular carcinoma (HCC) is often infeasible due to unfavorable location and poor conspicuity. Those small HCCs can be treated with combined transarterial chemoembolization (TACE) and RFA. Purpose To evaluate long-term outcomes of combined TACE and RFA for small treatment-naïve HCC infeasible for US-guided RFA. Material and Methods Between February 2009 and January 2014, 69 patients with small (≤3 cm) HCC infeasible for US-guided R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Therefore, placement of RF electrodes into the tumor would be possible under US, CT, or fluoroscopy guidance. In a previous study[45], as expected, the technical success rate of combined treatment was as high as 99% (93/94) in HCCs 3 cm or smaller. However, more data are needed to assess whether combined treatment is also effective for sub-centimeter HCCs.…”
Section: Management Of Sub-centimeter Recurrent Hccsupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, placement of RF electrodes into the tumor would be possible under US, CT, or fluoroscopy guidance. In a previous study[45], as expected, the technical success rate of combined treatment was as high as 99% (93/94) in HCCs 3 cm or smaller. However, more data are needed to assess whether combined treatment is also effective for sub-centimeter HCCs.…”
Section: Management Of Sub-centimeter Recurrent Hccsupporting
confidence: 79%
“…Recently, Hyun et al[45] reported that combined transarterial chemoembolization (TACE) and RF ablation is an effective treatment for HCCs that are not suitable for US-guided RF ablation. Theoretically, intratumoral accumulation of radio-opaque iodized oil used in TACE can make the target tumor visible by either fluoroscopy or CT images.…”
Section: Management Of Sub-centimeter Recurrent Hccmentioning
confidence: 99%
“…2123 Indeed, studies of combined therapy for small and intermediate-sized HCC have demonstrated good feasibility and tolerability, enhanced local control, low levels of tumor progression, and improved survival. 24,25 However, many of these studies have used radiofrequency ablation or only single-antenna MWA.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter arterial chemoembolization (TACE) is a minimally invasive and nonsurgical technique to treat advanced tumors through introducing embolic reagents and chemotherapeutic drugs into arteries and capillaries. [ 1–5 ] Although many interesting embolic materials have been used for TACE, their inherent defects still limited their clinical application. For examples, the solid embolic reagents, such as polyvinyl alcohol (PVA), gelatin sponge, and alginic acid microspheres, are demonstrated of desired mechanical strength, but they underperform in blocking peripheral vessels along with collateral circulatory formation due to the limited size distribution ( Scheme A).…”
Section: Introductionmentioning
confidence: 99%